2021
DOI: 10.2147/cmar.s272851
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0031242 Silencing Mitigates the Progression and Drug Resistance in DDP-Resistant Hepatoma Cells by the miR-924/POU3F2 Axis

Abstract: Background: Circular RNAs (circRNAs) have been implicated in the progression and chemoresistance development of hepatocellular carcinoma (HCC). However, the precise parts of circ_0031242 in HCC chemoresistance are still not fully understood. Methods: The levels of circ_0031242, miR-924 and POU class 3 homeobox 2 (POU3F2) were detected by quantitative real-time polymerase chain reaction (qRT-PCR) assay or Western blot analysis. IC 50 value for cisplatin (DDP) and cell viability were measured by the cell countin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…They found that the miR-924/POU3F2 axis could be regulated to promote the cisplatin resistance, proliferation, and invasion of hepatoma cells by circ_0031242. The same results were observed in xenografts ( Fan et al, 2021 ). The upregulation of the circ_0000517 expression in cisplatin-resistant hepatocellular carcinoma cells could promote cell cycle arrest and apoptosis through the miR-328-3P/ARID4B axis.…”
Section: Introductionsupporting
confidence: 81%
“…They found that the miR-924/POU3F2 axis could be regulated to promote the cisplatin resistance, proliferation, and invasion of hepatoma cells by circ_0031242. The same results were observed in xenografts ( Fan et al, 2021 ). The upregulation of the circ_0000517 expression in cisplatin-resistant hepatocellular carcinoma cells could promote cell cycle arrest and apoptosis through the miR-328-3P/ARID4B axis.…”
Section: Introductionsupporting
confidence: 81%
“…For example, miR‐924 was found to be abnormally expressed in hepatocellular cancer and inhibited the metastasis of hepatocellular cancer cells 32 . Moreover, miR‐924 was expressed to a low extent in hepatoma cells and suppressed cisplatin resistance, which acted as a downstream gene of circ_0031242 in hepatoma progression 33 . In NSCLC, miR‐924 exerted a tumor‐suppressive action, repressing the metastasis and multiplication of H1299 and A549 cells 18 .…”
Section: Discussionmentioning
confidence: 99%
“…32 Moreover, miR-924 was expressed to a low extent in hepatoma cells and suppressed cisplatin resistance, which acted as a downstream gene of circ_0031242 in hepatoma progression. 33 In NSCLC, miR-924 exerted a tumor-suppressive action, repressing the metastasis and multiplication of H1299 and A549 cells. 18 Consistently, low expression miR-924 in NSCLC tissues and cells was also found in the present study, and circ_0006006 acted as a sponge for miR-924, thereby regulating its expression.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have confirmed that circRNAs impact HCC cisplatin resistance. For example, circ_0031242 enhances cisplatin resistance in HCC by sponging miR-924 to enhance the expression of POU class 3 homeobox 2, a promoter of tumor progression and metastasis[ 112 , 113 ]. Additionally, pyruvate dehydrogenase kinase 1 (PDK1), a glycolytic enzyme, is closely associated with chemotherapy resistance[ 114 ].…”
Section: Role Of Circrnas In Hccmentioning
confidence: 99%